Analysis of Oil Price and Exchange Rate in Indonesia - wahyudi, Heru; Andriyanto, R. Weddie; Tresnaningtyas, Armeita; Sumanda, Kamadie; Palupi, Widia Anggi (International Journal of Energy Economics and Policy, 2023)
This research aims to find out the long-term and short-term effects of the oil price variable on the exchange rate, as well as the variables of foreign exchange reserves, relative money supply, relative GDP, and interest rates relative to the exchange rate in Indonesia. The analytical method used is the Error Correction Model (ECM). This study's results indicate a significant negative effect between the variables of foreign exchange reserves, relative GDP, and relative interest rates on exchange rates in the long term and short term. There is an insignificant positive relationship between oil prices and the exchange rate in the long term and a significant positive relationship in the short term. There is an insignificant negative effect between the money supply relative to the exchange rate in the long term and a significant negative relationship in the short term.